ANALISIS EFEKTIVITAS PEMUNGUTAN RETRIBUSI PELAYANAN PASAR DI PASAR MODERN PERTOKOAN BEKASI JUNCTION TAHUN 2021-2023 - Hidayati, Mainita; Gunawan, Elisha Agustina (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The phenomenon in this study is the effectiveness of the acceptance of the realization of market service fees at the Bekasi Junction Shopping Center which continues to decline, the lack of understanding of mandatory fees related to the collection of market service fees at the Bekasi Junction Shopping Center modern market. The purpose of this study was to determine and analyze the effectiveness, obstacles, and efforts that can be made in collecting market service fees at the Bekasi Junction Shopping Center modern market in 2021-2023. This research method uses a descriptive qualitative approach. The results of this study indicate that the effectiveness of collecting market service fees at the Bekasi Junction Shopping Center modern market in 2021-2023 is included in the ineffective category. This can be seen from the effectiveness ratio in 2021-2023 which was not achieved according to the effectiveness category. Reviewed based on the achievement of objectives, integration and adaptation are said to be ineffective because market governance still requires innovation and improvement, socialization is still needed regarding the importance of market service fee collection procedures, and the need for improving supporting infrastructure accompanied by trained human resources. Efforts that can be made include improving market governance and reviewing cooperation agreements between local governments and managers.